the Testing of Polymer Parameters for EOR Applications in Carbonate Reservoirs in The AF Field with High Temperature and Salinity - Agustina Prihantini; Nurkhozin Adhi Nugroho; Ananda Fevi Silvia (Jurnal Migasian, 2024)
The AF field is one of the 34 candidates determined by the government to be able to carry out the EOR stage to extract unproduced oil residues with a water salinity value of 29400.39 mg/L resulting in an API value of 23. This field has a temperature of 82 ℃, where is said to be medium temperature. The method in this test is to use a laboratory scale by screening polymers by conducting tests to verify field data. This test has the goal of knowing the formula for making polymer and its stages, knowing the parameters of testing this polymer and knowing the results of this test with the various parameters tested. Screening carried out included a compatibility test with good results, namely having clear visuals and one phase, the viscosity obtained, which varied with viscosity versus concentration where if the concentration was high, the viscosity would also be high, and viscosity versus shear rate, namely where the shear rate decreased the viscosity went up, but in the tests I did at concentrations of 1000 ppm and 1500 ppm at speeds of 150 – 200 RPM there was an increase in the graphs due to air contamination with polymer and human error. At the screen factor testing stage, the results obtained are the higher the concentration and also the higher the viscosity, the time taken is also directly proportional. Whereas in the filtration test the data obtained was 1.02 at a concentration of 2500 ppm and a value of 0.80 at 2000 ppm, which is a good qualification or polymer screening, because the filtration ratio value must be below 1.2 and in the final stage, testing the thermal stability of the result is stable even though there is polymer degradation at 8.20%.